The implications of psychotherapeutic discourses for victims and offenders of female perpetuated child sexual abuse - Zisterer Meyer, Jenny (European Journal for Qualitative Research in Psychotherapy, 2021)
Although child sexual abuse has been studied extensively in the academic literature, research studies have often failed to contemplate the female child molester or to initiate specific protocols for the psychotherapeutic treatment of both offenders and victims of female perpetuated child sexual abuse. By analysing the transcribed corpus of six semi-structured interviews using Foucauldian discourse analysis, this article examines the ways in which expertise and authority play out in the language practices of six experienced psychotherapists around this contentious issue. Findings indicate that female child molesters are socially represented in varying and often contradictory ways and that practitioners may face ideological dilemmas when working therapeutically with this client group. Five main narratives emerged from the data: 1) A taboo subject 2) Avoiding the elephant in the room 3) Letting down the sisterhood 4) A discourse of contradictions and 5) The female paedophile as a ‘cloak and dagger figure’ or ‘loving caregiver’? Informed by a linguistic paradigm which views language as constructive rather than representative, this article draws attention to the effects and contingencies of current psychotherapeutic discourses on female perpetuated child sexual abuse. It aims to shed light on the potential complexities of recovery from this type of abuse and to point to new directions in the field of psychotherapeutic research.